Program Konservasi Mangrove di Pantai Glagah Wangi Demak Ditinjau dari Upaya Mencapai Sustainable Development Goals (SDGs) - Qo'im Rohmawati; Nanik Esti Wulandari; Ahmad Soleh; Rezki Widarti; Musyafiatun Musyafiatun; Grisselda Vania Putri; Fauzan Fauzan (Perkumpulan Kualitama Edukatika Indonesia, 2022)
On the north coast of Central Java, the abrasion area has reached 5,500 hectares spread over 10 regencies/cities. Abrasion is the erosion or reduction of land (beach) due to wave activity, currents and tides. In Tambakbulusan Village, Karangtengah Subdistrict, Demak Regency, there is a Glagahwangi beach which is affected by abrasion. This study uses an interview approach, observation, and documentation techniques, which then support data obtained from research journals, online media, and others. Based on these problems, a mangrove conservation program was carried out on the Glagahwangi beach in an effort to achieve the SDGs in the pillars of environmental development which is a national program launched by the government. With this program, it is hoped that the preservation of the surrounding environment will improve, the welfare and economy of the surrounding community will increase. The results show that the mangrove conservation program has a tremendous positive impact on the environment, society, and the economy around the coast. In terms of the environment, mangrove conservation can protect biodiversity, namely aquatic semi-terrestrial and terrestrial, the life of future generations, clean water salinity, absorb pollutants, reduce the greenhouse effect with the